IN ELEMENTARY SCHOOLS, MENTORING IS AN ATTEMPT TO CREATE A CULTURE OF QUALITY IN RESPONSE TO THE ENVIRONMENTAL CRISIS FACING CIVILIZATION - Septian, Christin Dwi Putri; Muhtar, Tatang (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2023)
Elementary schools are in a unique position to raise the next generation of environmentally conscious citizens in the face of an impending environmental crisis. The purpose of this paper is to investigate how mentoring programs might help these schools develop a culture of quality, which is characterized by ecological awareness and action.In an endeavor to create a quality culture in primary schools while responding to a humanitarian catastrophe, this study seeks to explain the function of mentorship. A comprehensive and efficient approach to education is required in light of the civilizational crisis, which encompasses moral degradation, social unrest, vulnerability, and environmental concerns. One method for addressing this issue and fostering a culture of excellence in primary schools is mentoring.Through mentoring, educators can foster a supportive learning atmosphere in which pupils are encouraged to resolve conflicts, cultivate empathy, and foster cooperation. Mentoring also increases parents' involvement in their kids' education, fostering cooperation between schools and families to raise educational standards. Mentoring can also assist in resolving issues that develop in the midst of a civilized crisis, such as an environmental crisis, by supplying the knowledge and abilities needed to handle it. Life on Earth depends on the process of photosynthesis. Through this process, light energy is transformed into chemical energy, which plants use to create oxygen and food. The oxygen that plants produce is essential for all other living things, including humans.